KAJIAN FAKTOR-FAKTOR YANG BERPENGARUH PADA KINERJA KEUANGAN PERUSAHAAN (STUDI PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX) - Karyadi, Iman; Ismangil, Ismangil; Djamilah, Siti (STIE Mahardhika, 2018)
The purpose of this study is to identify the factors that affect the financial performance of companies listed in the Jakarta Islamic Index (JII). The sample of this study is a company registered successively in JII period 2010-2014, issuing annual report and financial report period 2010 to 2014 and no loss. Of the 30 listed companies in JII in each period, there are 14 companies listed successively in 2010-2014, thus the number of observers is 70 observation. Factors that affect the financial performance of the company consists of 2 factors. The first factor, management of the balance sheet that is in the form of fixed assets, long-term debt, capital, liquidity and leverage. The second factor is good corporate governance (GCG) consisting of public ownership, institutional ownership and board size. The dependent variable is the companys financial performance in the form of return on asset (ROA) and return on equity (ROE). Analysis technique to test hypothesis using multiple linear regression. The results showed that liquidity, leverage and institutional ownership have positive and significant effect on ROA and ROE. The higher the liquidity, leverage and institutional ownership, the higher the ROA and ROE.